THE EFFECT OF SOCIODRAMA ON STUDENTSâ€™ ARABIC SPEAKING SKILL (AN EXPERIMENTAL STUDY AT SMA-IT AL-FATH PAYAKUMBUH) / ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙ…Ø«ÙŠÙ„ÙŠØ© Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… (Ø¯Ø±Ø§Ø³Ø© ØªØ¬Ø±ÙŠØ¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙØªØ Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù…ØªÙƒØ§Ù…Ù„Ø© Ø¨Ø§ÙŠØ§ÙƒÙ…Ø¨ÙˆÙ‡) - Orizza Sativa Azahra; Rizka Widayanti (IAIN Batusangkar, Indonesia, 2022)
This study aims to find out the effect of sociodrama on studentsâ€™ Arabic speaking skill at SMA-IT AL-Fath Payakumbuh. Experimental research of quantitative approach was used with pre-experimental design. Samples were 23 students of grade X at SMA-IT Al-Fath.Â Pre-test and post-test were administered to collect the data which then analyzed using t-test. Findings of the research described that t0 was 3.55 and ttableÂ was 1.71 at significance level of 5% and df was 22. It indicates that t0 is higher than ttÂ (3.55>1.71), H0 is rejected and Ha is accepted which means that there is a significant effect of sociodrama on studentsâ€™ Arabic speaking skill. Finally, it can be concluded that sociodrama is one technique that can be used to improve studentsâ€™ Arabic learning achievement, especially speaking skill.